Unionisation triggers tax incentives to attract foreign direct investment - Andreas Haufler; Ferdinand Mittermaier (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper analyses tax competition between a unionised and a non-unionised country for the location of an outside firm. We show that unionisation offers an extra incentive for the government to attract a foreign competitor to a concentrated domestic market, in order to affect the behaviour of the domestic union. This results in the unionised country's government offering a tax discount (or a subsidy premium) to the outside firm in excess of what is needed to compensate the investor for the higher union wage. In equilibrium, therefore, the unionised country can attract the outside firm even if it has other location disadvantages, such as a smaller home market.
Keywords: H87; H25; F21; J58; 330; Steuerwettbewerb; Gewerkschaftlicher Organisationsgrad; Direktinvestition; Steuerbegünstigung; Zwei-Länder-Modell; Theorie